Оцінка адаптаційної здатності видів колекції низькорослих і ґрунтопокривних трав'янистих багаторічників у Донецькому ботанічному саду НАН України - Krokhmal, I.I.; Pirko, I.F. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The range of tolerance to the thermal mode, contrast mode, ombromode and cryomode for the species from the collection of short-growing and soil-covering redivives of Donetsk Botanical Garden of the NAS of Ukraine has been determined. It has been found that in terms of the thermal mode submesotherms, mesotherms and macrotherms, whose area involves Western Europe, the Caucasus, Asia Minor, the Balkans, the Crimea, the Mediterranian, Iran and the European part of the former USSR, are best adapted to natural climatic conditions of the southeast of Ukraine; in terms of continentality the best species are hemioceanists, subcontinentalists and hemicontinentalists; in terms of the ombromode – subaridophytes, mesoaridophytes and semiaridophytes; in terms of cryomode – hemicryophytes. It has been suggested that suboceanists and oceanists are less well adapted to the conditions of the southeast of Ukraine as opposed to hemioceanists, hemicontinentals and subcontinentals. It follows that it is possible to anticipate successful introduction of redivives whose area refers to the regions of the globe with the thermal mode of 45 to 55 kcal·cm-2·year-1, the ombromode of –1600…–200 mm of precipitation, the cryomode of +6 to –6 °С.